Pengaruh Antara Faktor Intern dan Faktor Ekstern terhadap Motivasi Kerja pada Karyawan PT. Astra International, Tbk. Honda - Sulistyaningsih Alvianie; Suhaji Suhaji (STIE Widya Manggala, 2014)
This study aimed to determine wether the internal factor and ekxternal factor influenced employee motivation at PT. Astra International, Tbk. Honda Semarang. The population were all employees at PT. Astra International, Tbk. Honda Semarang,amounting to 375 employees, while the samples were taken 79 employees. The sampling technique used was convenience sampling. The data analysis technique used was multiple linear regression analysis. The results showed that, internal factor influenced employee motivation, seen from significant value 0.005 <0.05. While external factor didn't influence employee motivation, seen from significant value 0.083> 0.05.